JUSTIFICATION OF CRITERIA AND INDICATORS OF FORMATION OF THE DEONTOLOGICAL COMPETENCE OF FUTURE EDUCATION MANAGERS - Zadorozhna-Knyagnitska, Lenina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article presents the results of theoretical analysis of scientific works on the problems of deontological training of future specialists in higher education institutions. The result of this training is deontological competence as a complex subjective feature that determines the ability for the proper professional behavior and making effective decisions in deontologically determined situations of managerial interaction. The purpose of the research is to theoretically substantiate the criteria and indicators of the formation of the deontological competence of future specialists. To achieve this goal, the following research methods were used: terminological analysis, concretization and generalization of theoretical concepts in the philosophical, psychological and pedagogical works of domestic and foreign scientists. The article describes the results of the research. The criteria and indicators of forming education managers’ deontological competence at university master’s level are proved for the first in pedagogical science. The content of motivation, cognitive, activity-based criteria is revealed. The motivation criterion indicates the motivation for normative behavior, developed values that determine the proper performance of professional duties by education managers, their aims and needs as bearers of professional and moral values; cognitive criterion defines the degree of acquisition of deontological knowledge; technological criterion shows the degree of forming deontological abilities and skills.